El teatro como estrategia pedagógica para mejorar la convivencia en la escuela (2015)
The target of this research study is to describe the elements of the theater that make it to act as a pedagogical strategy to improve relationships in schools; specifically interpersonal relationships among students, which have been deteriorating in most educational institutions because, nonverbal verbal abuse and physical many times between them. This research takes as its central problem the way of using the theater as a teaching strategy which allows us the improvement of coexistence in the school as in the case of the “District Educational Institution Foundation Pies Descalzos” where we could see how it was possible to improve school relationships, specifically in sixth and seventh grade where it was found as the main problem of violence between peers, negative ways how students relate to others. To make this study possible was necessary to use the approach of joint research and among the cast results include the deterioration of relations between peers and indeed the use of theater as a teaching strategy that improves coexistence in the school and therefore facilitates students to learn to communicate in a different way; where dialogue, body, gestures, emotions helps them identify new ways to solve everyday conflicts, not only in the classroom also outside it, learning to live together in a harmonious way feeling what the other person may feel if mistreated verbal or nonverbal physical.